The multidisciplinary approach to eosinophilia - Thomsen, Gunhild Nynke; Christoffersen, Mette Niemann; Lindegaard, Hanne Merete; Davidsen, Jesper Rømhild; Hartmeyer, Gitte Nyvang; Assing, Kristian; Mortz, Charlotte G.; Martin-Iguacel, Raquel; Møller, Michael Boe; Kjeldsen, Anette Drøhse; Havelund, Troels; El Fassi, Daniel; et al. (Frontiers in Oncology, 2023)
Eosinophilic granulocytes are normally present in low numbers in the blood stream. Patients with an increased number of eosinophilic granulocytes in the differential count (eosinophilia) are common and may pose a clinical challenge, because conditions with eosinophilia occur in all medical specialties. The diagnostic approach must be guided by a thorough medical history, supported by specific tests as the rationale for an individual treatment. The neoplastic (primary) eosinophilia is identified by one of several unique acquired genetic causes. In contrast, the reactive (secondary) eosinophilia is associated with a cytokine stimulus in a specific disease, whereas the idiopathic eosinophilia is a diagnosis by exclusion. The rational treatment is directed towards the disease in secondary cases and has paved the way for targeted treatment against the driver in primary eosinophilia, whereas idiopathic cases are treated if needed by principles in eosinophilia, originating in clonal drivers. The vast majority of patients are diagnosed with secondary eosinophilia and are managed by the relevant specialty – e.g., rheumatology, allergy, dermatology, gastroenterology, lung medicine, hematology, or infectious disease. The overlap in symptoms and risk for irreversible organ involvement in eosinophilia, irrespective of the cause, justifies that patients without a diagnostic clarification or who do not respond to adequate treatment should be referred to a multidisciplinary function, anchored at a hematological department for evaluation. This review presents the pathophysiology, manifestations, and differential diagnosis, diagnostic work-up, and management of (adult) patients with eosinophilia. The purpose is to present eosinophilia in a clinical context, and in this way justify and inspire the establishment of a multidisciplinary team of experts from diagnostic and clinical specialties regionally to support the second opinion. The target patient population requires highly specialized laboratory analysis and therapy, and occasionally have severe eosinophil-induced organ dysfunctions. An added value of a centralized, clinical function is to serve as a platform for education and research to further improve the management of patients with eosinophilia. Primary and idiopathic eosinophilia are key topics in the review, which also addresses current research and discusses outstanding issues in the field.